2004
DOI: 10.1002/jsfa.1768
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gas transport properties and the histology of apple

Abstract: The relation between skin resistance to gas diffusion, diffusivity and several histological characteristics of apple cvs Braeburn and Jonica was investigated. Large discrepancies were found between the skin resistance values measured by the efflux method and a diffusion method. It is believed that these discrepancies are due to the invalidity of Graham's law in tightly packed tissue, the existence of internal gas gradients and the types of tissue measured in the two methods. The differences between cultivars i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 31 publications
5
45
1
Order By: Relevance
“…Fruit subjected to AVG + ABS possibly had higher cell integrity and stability, which resulted in higher gas diffusion (Schotsmans et al, 2004). It is noteworthy that fruit which had high gas diffusion showed higher internal space, and these two parameters had a positive Pearson correlation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fruit subjected to AVG + ABS possibly had higher cell integrity and stability, which resulted in higher gas diffusion (Schotsmans et al, 2004). It is noteworthy that fruit which had high gas diffusion showed higher internal space, and these two parameters had a positive Pearson correlation.…”
Section: Resultsmentioning
confidence: 96%
“…If, for any reason, gas exchange is hindered, the internal atmosphere changes, which can result in some physiological disorders (flesh browning and mealiness) and in a decrease of fruit quality after storage (Franck et al, 2007). Gas diffusion on apple varies according to the cultivars, harvest dates, and storage time (Schotsmans et al, 2004). Some growth regulators in use in Brazilian apple production can affect the gas diffusion, due to alterations on normal growth of fruit, on its development, and on the gas exchange, which lead to physiological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits treated with AVG, AVG + 1-MCP and AVG + ABS had the highest gas diffusion rate throughout the apple pulp. The higher gas diffusion of these fruits is a result of the higher cell wall integrity, once the gas diffuses through the intercellular spaces formed by the cell wall (Schotsmans et al, 2004;Verboven et al, 2007). One of the main problems during apple storage is the incidence of physiological disorders, such as mealiness.…”
Section: Quality Analysis After 8 Months Of Storagementioning
confidence: 99%
“…Later on, Verboven et al (2008) used high-resolution phase tomography (making use of synchrotron radiation) to explore the 3-D structure and cellular arrangements of pome fruit tissues in their natural state (i.e., with high water content) up to sub-micrometer resolution. For this study, pome fruits like; apple and pear were selected because their gas exchange properties have been shown to be very different and closely related to their storage lives (Schotsmans et al 2004;Ho et al 2006a, b;Franck et al 2007;Ho et al 2008). Results obtained by Verboven et al (2008) revealed very clearly that the apple fruit had more voids than pear.…”
Section: Gaseous Exchange and Factors Affecting The Composition Of Thmentioning
confidence: 99%